2019
DOI: 10.1371/journal.pone.0215929
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and reproducible somatic embryogenesis and micropropagation in tomato via novel structures - Rhizoid Tubers

Abstract: A dual in vitro regeneration system consisting of indirect organogenesis and somatic embryogenesis (SE), applicable to several varieties of tomato— Solanum lycopersicum (cv. Riogrande , cv. Roma , hybrid 17905 and model cv. M82 ) has been established. This system is both improved and highly reproducible compared to current methods. Callus initiation, plant regeneration and S… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
16
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 68 publications
(82 reference statements)
4
16
0
1
Order By: Relevance
“…BA was the most effective among the four cytokinins employed in axillary shoot regeneration in A. lupulina similar to that reported by Sivanesan and Park [ 18 ]. TDZ is believed to be the best synthetic cytokinin present for the regeneration of numerous plant systems [ 19 , 20 ]. High cytokinin activity of TDZ inhibits shoot elongation; however, it is conducive to the formation of somatic embryos [ 15 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…BA was the most effective among the four cytokinins employed in axillary shoot regeneration in A. lupulina similar to that reported by Sivanesan and Park [ 18 ]. TDZ is believed to be the best synthetic cytokinin present for the regeneration of numerous plant systems [ 19 , 20 ]. High cytokinin activity of TDZ inhibits shoot elongation; however, it is conducive to the formation of somatic embryos [ 15 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cytokinins in plants stimulate cell division, bud initiation, and proliferation ( Van Staden et al, 2008 ). In vitro regeneration of tomato has been significantly affected by the explants, genotypes, and PGR concentrations and combinations used in the culture medium ( Alatar et al, 2017 , Prihatna et al, 2019 , Saeed et al, 2019 , Vinoth et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The results confirmed that ZEA was a superior cytokinin concerning multiple shoot induction among three plant growth regulators tested. Successful regeneration procedures have been reported using different explant types of many tomato genotypes on medium augmented with ZEA ( Gupta and Van Eck, 2016 , Saeed et al, 2019 ). In shoot induction medium containing ZEA, all the explants generated the optimum number of shoots (from 2.86 to 26.76 shoots) after two successive subcultures ( Table 1 , Table 2 , Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…No study so far assigns a functional role for a specific metabolite in P. indica mediated growth promotion across plants. Tomato ( Solanum lycopersicum L.) is one of the most important vegetables grown worldwide with 177 million ton production (Saeed et al, 2019). However, Tomato has been least explored for its interaction with P. indica and beneficial effects.…”
Section: Introductionmentioning
confidence: 99%